Pengaruh Organisasi Kemahasiswaan Terhadap Prestasi Belajar Mahasiswa Prodi Pendidikan Ekonomi FKIP Untan Pontianak - Rivaldi, Septian; ., Aminuyati; Khosmas, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: HMJ P.IPS FKIP Untan student organizations is a student organization for economic education FKIP Untan as a place to develop interests and talents and organizational skills and academic. A common problem in this study is